ZEOLITE-CONTAINING THRILL IN THE PREVENTIVE TREATMENT OF EXPERIMENTAL CARIES - Игорь Васильевич Малов (Medicina v Kuzbasse, 2020)
In order to assess the effectiveness of the use of zeolite tripoli, groups of animals were formed depending on the use of this mineral, as well as the presence of a cariogenic diet. As a result, four groups of laboratory rats were included in the work. The first group included 26 rats fed the basic feed. The second group (n = 26) consisted of animals, which, together with the basic feed, received a zeolite-containing tripoli in the amount of 1.5 g per kilogram of body weight in addition to the standard diet. The third group (n = 26) was on a cariesogenic diet, and the fourth group (n = 26) was on a cariogenic diet; however, the rats of this group, together with the basic feed, were also given a zeolite tripoliin the amount of 1.5 g per kilogram of body weight. At the initial stage of the experiment, laboratory animals did not differ significantly from each other. However, after the experiment, we identified certain differences that indicate the effectiveness of the use of zeolite-containing Tripoli. Analysis of the biochemical parameters of the gums revealed statistically significant differences with respect to the data series. The effect of zeolite-containing Tripoli on the concentration of malonic dialdehyde, the total proteolytic activity of catalase and urease has been established. The data on the positive effect of zeolite trefoil on the biochemical parameters of blood, gums, as well as the content of saliva minerals were obtained. The above data are consistent with the results of the morphological study of the teeth of the studied animals.